Circular RNAs in Blood Malignancies - Perez de Acha, Olivia; Rossi, Martina; Gorospe, Myriam (Frontiers in Molecular Biosciences, 2020)
Circular (circ)RNAs influence a wide range of biological processes at least in part by interacting with proteins and microRNAs. CircRNAs expressed in the hematopoietic compartment have been increasingly recognized as modulators of physiological and pathological features of hematopoetic stem cell (HSC)-derived populations. In particular, several circRNAs were found to enhance or suppress tumor progression in blood malignancies such as leukemias and lymphomas. Moreover, numerous circRNAs have been proposed to help confer resistance to the conventional treatments used in hematopoietic cancers. Here, we review the most important circRNAs described thus far in acute myeloid leukemia (AML), chronic myeloid leukemia (CML), acute lymphoblastic leukemia (ALL), chronic lymphocytic leukemia (CLL), lymphomas, and multiple myeloma (MM). We discuss the usefulness of circRNAs as diagnostic and prognostic markers and their potential value as therapeutic targets.